The Eastern Policy of the European Union. The Role of Poland (Politeja, 2016)
The paper aims at outlining the EU policy – including Poland’s role in its development – towards the Union’s eastern neighbours encompassed by the European Neighbourhood Policy and Eastern Partnership. The situation of the EU’s eastern neighbours has become considerably complicated in the last two years (2014-2015). The Euromaidan revolution and war in the Donbas have led the EU Member States to direct their efforts towards stabilising the situation in Ukraine. As a consequence, discussions of future prospects and the EU policy towards Eastern Europe and the South Caucasus have been set aside. In addition, wars and conflicts occurring in the south of Europe along with the immigrants flooding southern EU Member States have led to the eastern neighbours and their problems being neglected (despite the fact that Ukraine is engulfed in war).